Pedagogical Content Knowledge of Out-Of-Field Junior High School Teachers in the Division of Angeles City Philippines - Renz Camaya; Elvira Balinas (Future Science / FSH-PH Publications, 2026)
This study examined the profile and pedagogical content knowledge (PCK) of out-of-field junior high school (JHS) teachers in the Division of Angeles City, Philippines. With the use of total enumeration, 110 respondents served as respondents. Data gathering was done with the use of Google Form. Through descriptive statistics, data were presented in percentage, frequency, mean, and standard deviation. Results revealed that most respondents were new teachers (21–30 years), holding a Bachelor of Secondary Education major in English. A majority of the respondents don’t have graduate studies degrees or units, with only a small number having earned master’s or doctoral degrees. The most commonly handled out-of-field subject is Values Education/Edukasyon sa Pagpapakatao. Most participants have one to three years of teaching experience and were primarily designated as Teacher I. It is further indicated that out-of-field JHS teachers demonstrated high levels of pedagogical knowledge, content knowledge, and pedagogical content knowledge. JHS teachers showed particular strength in improving lesson content, connecting lesson topics to enhance meaningful learning, relating lessons to real-life contexts, employing higher-order questioning techniques aligned with DepEd standards, and effectively using their voice during instruction. The results further suggest that despite teaching out-of-field, respondents exhibit a high level of pedagogical content knowledge, highlighting their instructional competence and adaptability in addressing curriculum and learner needs.